The Influence of Transformational Leadership, Job Satisfaction and Organizational Citizenship Behavior on Employee Engagement at BPRS HIK Parahyangan - Nadya Mahri; Nina Nurani (Dinasti International Journal of Education Management And Social Science, 2025)
Employee engagement has become a concern in a competitive world and is a very important issue for organizations. This study aims to determine the partial effect of transformational leadership, job satisfaction, organizational citizenship behavior on employee engagement at BPRS HIK Parahyangan Bandung. This study uses a quantitative approach with survey and questionnaire methods as data collection instruments. The sample of this study is a saturated sample consisting of 99 respondents. Data processing of the research results using SPSS version 26 using data analysis is carried out using linear regression techniques to assess the effect of independent variables on dependent variables. The results of the study indicate that transformational leadership is partially included in the good category and has a positive and significant effect on employee engagement, as well as job satisfaction is partially included in the good category and has a positive and significant effect on employee engagement, and organizational citizenship behavior is also partially positive and significant effect on employee engagement.